Diseño de un modelo a escala laboratorio de un reactor anaeróbico uasb para las aguas residuales institucionales de la Corporación Universitaria de la Costa (2001)
The design of the model climbs laboratory for the treatment of institutional wastes water of the University Corporation of the Coast, it was realized bearing in mind certain parameters that help to carry out this project of effective and truthful form. Referring to the institutional wastes water of the University Corporation of the Coast, it is possible to be said that they present suitable physical and chemical characteristics like temperature, nutrients, pH, solid, etc. there are treated by a reactor low UASB climatic and environmental conditions of the Atlantic Coast. The wastes water are the result of the use of the water for different ends. As a result of this use (commercial, domestic, industrial, agricultural, institutional), the water gathers matters in suspension and dissolved that alter its properties. Depending on the type of use (servants, TV/radio commercial, institutional), the wastes water present very different characteristics